Paneth cell α-defensins in enteric innate immunity - Ouellette, André Joseph (SP Birkhäuser Verlag Basel, 2011)
Paneth cells at the base of small intestinal crypts of Lieberkühn secrete high levels of α-defensins in response to cholinergic and microbial stimuli. Paneth cell α-defensins are broad spectrum microbicides that function in the extracellular environment of the intestinal lumen, and they are responsible for the majority of secreted bactericidal peptide activity. Paneth cell α-defensins confer immunity to oral infection by Salmonella enterica serovar Typhimurium, and they are major determinants of the composition of the small intestinal microbiome. In addition to host defense molecules such as α-defensins, lysozyme, and Pla2g2a, Paneth cells also produce and release proinflammatory mediators as components of secretory granules. Disruption of Paneth cell homeostasis, with subsequent induction of endoplasmic reticulum stress, autophagy, or apoptosis, contributes to inflammation in diverse genetic and experimental mouse models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-011-0714-6) contains supplementary material, which is available to authorized users.